FROM RONGGENG TO WHITE CROCODILE: NARRATIVE, PERFORMATIVITY, AND CULTURAL ECOLOGY IN THE MYTH OF SAEDAH–SAENIH FROM INDRAMAYU - Lailatunnuryah, Aprilia; Basori, B (Jurnal Tradisi Lisan Nusantara, 2025)
This article discusses the myth of Saedah-Saenih from Indramayu as a form of oral literature that is alive and continues to be reproduced in various cultural mediums. Through a qualitative-ethnographic approach, this study analyzes written and oral texts, tarling performances, school plays, local films, and ritual practices on the Sewo Bridge. The results showed that despite variations in the details of the storytelling, the core motives—the cruel stepmother, the abandonment of the child, the supernatural pact, and the metamorphosis into the elements of nature—were always present as the basic structure of the narrative. Performative analysis shows that this myth is not only understood as a text, but also as a cultural event that involves interaction between speakers, audiences, and social spaces. Cultural ecology reveals the close connection between mythical figures and the landscape of the Sewo River, where the transformation into white crocodiles, trees, pring ori, and bale kambang confirms the role of myth as a cosmological map of the Indramayu people. From a social and gender point of view, the story reflects ambivalence: on the one hand it reinforces the stereotype of good and bad women, on the other hand it implies an attempt at symbolic resistance through the character of Saenih trying to get out of the snare of poverty. This myth serves a dual purpose: as an ideological device that affirms family values, morality, and religiosity, as well as an arena of cultural resistance that maintains local identity in the midst of modernization. Thus, the Saedah–Saenih myth shows that oral literature not only functions as a textual heritage, but also as a dynamic, meaningful, and relevant cultural practice in shaping the identity of contemporary society.